Pengembangan Model Elaborasi Untuk Kecakapan Text Writing Melalui Audio Visual Pada Pelajaran Bahasa Inggris - Aprizal, -; Umar, Syahwani; Usman, Andi (Universitas Tanjungpura, 2016)
Aims to help teachers of English in overcoming difficulties and student learning in English lessons . Efforts English teacher with the development model through the elaboration of Media Audio Visual . Techniques of collecting data using questionnaires , observation and interviews . Implementation of the trial , as well as the acquisition of skills competency test text writing . All data collected were analyzed quantitatively and qualitatively using a simple matter of percentages . Based on the results of the discussion can be concluded that the results